IMPLEMENTASI RESCHEDULING, RECONDITIONING DAN RESTRUCTURING SEBAGAI UPAYA PENYELESAIAN PEMBIAYAAN BERMASALAH PADA MASA PANDEMI COVID-19 DI BRI SYARIAH KCP MOJOSARI - Bariroh, Rusydah; Mukhlisuddin, Ahmad; Kusrini, Nurul Azizah Ria (Universitas Siliwangi, 2022)
The outbreak of the Covid-19 virus in Indonesia caused instability in the economy, therefore the OJK issued a stimulus policy for restructuring financing for banks. Non-performing Financing (NPF) at BRI Syariah is relatively low during the pandemic by implementing financing restructuring. The purpose of this study was to find out how to implement rescheduling, reconditioning and restructuring as an effort to resolve financing problems during the pandemic at BRI Syariah KCP Mojosari. The type of research used is qualitative research with the data used coming from interviews with the Branch Manager, Account Officer, and Team leader sections which are then analyzed using descriptive qualitative analysis methods with an inductive mindset that is based on specific facts for later research, organizing and analyzed so that it can be applied in general. The results of the study show that the implementation of rescheduling, reconditioning and restructuring is carried out since the customer is included in the collectability category 2 or in Special Attention (DPK). The cause of customers restructuring is due to a decrease in turnover or income due to the impact of the Covid-19 pandemic. The implementation of restructuring at BRI Syariah KCP Mojosari during the pandemic can be done in two ways, namelyÂ rescheduling and reconditioning. Procedure for applying for customer financing restructuring by attaching a letter of application for relief without paying administrative fees